The Resilience of Individuals with Physical Disabilities as Heads of Household in Facing the Impact of COVID-19 in Bogor City - Pribowo Pribowo; Dela Vinka Ariska (Khazanah Sosial, 2025)
The COVID-19 pandemic has had a profound impact on all segments of society, including individuals with disabilities. This study seeks to examine the resilience strategies employed by persons with disabilities who serve as heads of households in navigating the challenges brought about by the pandemic. Utilizing a qualitative approach with a descriptive method, the research involved three purposively selected participants who were individuals with disabilities who assumed the role of family heads. Data were analyzed through thematic analysis by categorizing and organizing the information into meaningful patterns and themes. The results indicate that the pandemic exacerbated economic vulnerabilities among participants, prompting adaptive responses such as enhanced intra-family communication and the strategic management of income sources. Additionally, the study highlights the role of collective resilience fostered through the Indonesian Association of Persons with Disabilities (PPDI) in Bogor City. The organization functions as a vital support system, offering emotional and practical assistance and instilling a sense of hope and agency among its members to overcome economic hardship and pursue sustainable well-being.